2010
DOI: 10.29302/oeconomica.2010.12.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Jones, Dechow And Kasznik Models Significance In The Romanian Economic Environment

Abstract: This study intends to be a first step into an attempt of measuring the earnings management using an econometric model valid for the Romanian specificities by trying to establish the level of significance of three acknowledged econometric models: Jones (1991), Dechow et al. (1995) and Kasznik (1999) on Romanian economic environment. Given the above mentioned premises, the study was conducted using the Romanian listed companies (active on the Bucharest Stock Exchange) selected by a main criteria: discrepancy be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
3
5
0
Order By: Relevance
“…Meanwhile absolute growths of operating expenses (∆COST) confirmed their expected positive correlations with total accruals (TACC). Consistently with the previous studies (Matis et al, 2010), there were observed positive relationships between the difference amid changes in sales revenues and changes in net account receivables (∆REV-∆REC) and total accruals (TACC).…”
Section: The Assessment Of Accrual Models Using the Time Series Data Approachsupporting
confidence: 90%
See 1 more Smart Citation
“…Meanwhile absolute growths of operating expenses (∆COST) confirmed their expected positive correlations with total accruals (TACC). Consistently with the previous studies (Matis et al, 2010), there were observed positive relationships between the difference amid changes in sales revenues and changes in net account receivables (∆REV-∆REC) and total accruals (TACC).…”
Section: The Assessment Of Accrual Models Using the Time Series Data Approachsupporting
confidence: 90%
“…Bešlic et al (2015), analysing the predictive power of the modified Jones model in the Serbian economic environment, show that this model is not sufficient and there is a need for its further modification. Comparable conclusions were reached by Matis et al (2010) who compared the existing accrual-based models to detect manipulation of financial reporting on a sample of companies listed on the Bucharest Stock Exchange, and Islam et al (2011) who examined the modified Jones model to detect earnings management in the context of the Bangladesh capital market.…”
Section: The Analysis Of Relationships Between Discretionary Accruals and The Frequency Of Big Bath And Small Net Income Increasescross-smentioning
confidence: 99%
“…The other study, Matis et al (2010), makes an attempt of measuring the earnings management using an econometric model valid for the Romanian specificities by trying to establish the level of significance of three acknowledged econometric models: Jones (1991), Dechow et al (1995) and Kasznik (1999) on Romanian economic environment. Their analyses lead to the conclusion that Jones model (1991) was found to be significant for Romanian economic environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These emphasize the correlation between intangible assets and company performance expressed by annual average market price, price/earnings ratio and earnings per share (Purcărea and Stancu, 2011). Other models analyze companies' performance on the base of correlation between net profit and cash-flow (Matis et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%